Concepts Associated with Health from the Perspective of Sustainable Development (2012)
ABSTRACT : The concept of health is a social construction defined by the historical-cultural contexts of societies. At the moment, this context is characterized by global challenges such as climate change, energy crisis, the north-south divide, and poverty, among others. In view of these challenges, sustainable development has emerged as a proposal to cope with these drawbacks of the Western development model. In this sense, it is plausible to suppose, in accordance with a new global scenario of sustainable development, that a new conception of health is also emerging. For that reason, this paper aims at identifying this renewed concept of health, together with related concepts which are mentioned in the official documents on sustainable development originated in the world summits. Despite the fact that the concepts of health and sustainable development have been understood as being equivalent, none of the aforementioned official documents has provided societies with an explicit concept of health. It was verified that the concept of health has been associated with that of need satisfaction and preservation of ecosystems, whereas the construct of illness is associated with the concepts of poverty and high consumption levels. Finally, it is concluded that health is an intermediate goal of sustainable development and not an end in itself.